Runaway kids and teenage prostitution : America's lost, abandoned, and sexually exploited children - Flowers, R. Barri (Ronald Barri) (Contributions in criminology and penology ;, 2001)
This concise and accessible new text examines the correlations between runaway children and teenage prostitution in the United States from a criminological, sociological, and psychological perspective. The author takes a systematic approach to defining and describing the differences between youth who run away from home and those who leave institutional settings and distinguishes the difference between runaway and throwaway children. A careful examination of teenage prostitution among girls and boys helps to illuminate the special problems faced by children who have run away. In addition, the a.